2008
DOI: 10.1103/physrevlett.101.117208
|View full text |Cite
|
Sign up to set email alerts
|

Mott Relation for Anomalous Hall and Nernst Effects inGa1xMnxAsFerromagnetic Semiconductors

Abstract: The Mott relation between the electrical and thermoelectric transport coefficients normally holds for phenomena involving scattering. However, the anomalous Hall effect (AHE) in ferromagnets may arise from intrinsic spin-orbit interaction. In this work, we have simultaneously measured AHE and the anomalous Nernst effect (ANE) in Ga 1-x Mn x As ferromagnetic semiconductor films, and observed an exceptionally large ANE at zero magnetic field. We further show that AHE and ANE share a common origin and demonstrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
149
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(163 citation statements)
references
References 18 publications
11
149
2
1
Order By: Relevance
“…Calculations in the disorder-free case successfully predict the qualitative features of the AHE (the sign and rough magnitude of σ xy ) in different III-V DMS materials. As mentioned earlier, recent experiments [11,13] carried out at high temperatures (T ∼ 10−15 K) have been interpreted using this picture of an intrinsic AHE in Ga 1−x Mn x As, albeit with the idealized assumption that compensation is absent. In our sample set, we estimate p to be in the range of 10-60% of the total Mn dopant concentration, indicating a high degree of compensation due to the presence of interstitials.…”
Section: Scaling Analysis Of the Anomalous Hall Effect At Low Temperamentioning
confidence: 99%
See 2 more Smart Citations
“…Calculations in the disorder-free case successfully predict the qualitative features of the AHE (the sign and rough magnitude of σ xy ) in different III-V DMS materials. As mentioned earlier, recent experiments [11,13] carried out at high temperatures (T ∼ 10−15 K) have been interpreted using this picture of an intrinsic AHE in Ga 1−x Mn x As, albeit with the idealized assumption that compensation is absent. In our sample set, we estimate p to be in the range of 10-60% of the total Mn dopant concentration, indicating a high degree of compensation due to the presence of interstitials.…”
Section: Scaling Analysis Of the Anomalous Hall Effect At Low Temperamentioning
confidence: 99%
“…Our study is restricted to samples whose resistivity lies in a regime 2 mΩ.cm < ∼ ρ xx < ∼ 10 mΩ.cm where other studies [11,13] have observed an AHE scaling exponent α = 2 at T ≥ 4.2 K. These observations have been interpreted as an insensitivity to disorder and thus as a signature of the intrinsic mechanism [11], in agreement with theoretical predictions made in the disorder-free limit [9]. However, we argue that unlike metallic ferromagnets where the Drude approximation works well at helium temperatures, the complex non-monotonic temperature dependence of the resistivity in Ga 1−x Mn x As provides strong motivation for systematic measurements at lower (dilution fridge) temperatures where impurity scattering is dominant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend has also triggered renewed interest in the anomalous Nernst effect (ANE) in ferromagnetic metals [3][4][5][6][7]15 , which is the spontaneous transverse voltage drop induced by heat current and is known to be proportional to magnetization (Fig. 1a).…”
mentioning
confidence: 99%
“…This anomalous Nernst e ect has been considered to be proportional to the magnetization [1][2][3][4][5][6][7] , and thus observed only in ferromagnets. Theoretically, however, the anomalous Nernst e ect provides a measure of the Berry curvature at the Fermi energy 8,9 , and so may be seen in magnets with no net magnetization.…”
mentioning
confidence: 99%